Survey of Medical Facilities in Epilepsy Care in Thailand - Wangphonphatthanasiri K (Journal of The Department of Medical Services, 2020)
Background: Epilepsy is common neurological disorder. Most epileptic patients could have seizure remission if appropriate epilepsy treatments are accessible. However, in Thailand, medical facilities in epilepsy care have not been provided adequately in all over regions. 58% of these patients, especially in rural regions, could not get proper medical care. Therefore, to improve treatment gap problem, basic medical facilities in epilepsy care need to be evaluated. Objectives: To survey the medical resources in epilepsy care in secondary hospitals in Thailand. Methods: Data were collected from all secondary hospitals (center hospital(A), general hospital(S) in 12 public health service areas by postal questionnaire survey during August 1-November 1,2018 Results: 36 out of 83 secondary hospital postal questionnaires were sent back (43.37%). This survey revealed epilepsy as nearly one fourth of neurological diseases presenting in both outpatient and inpatient units. 80.6 % of these hospitals had at least one medical personnel who was specialized in epilepsy. Internists are the main key persons taking care of this group of patients. Advanced investigations such as CT, MRI brain and EEG were available 97.2%, 34.3% and 40% respectively. 88.6% of the hospitals had all 4 types of standard oral antiepileptic drugs and all hospitals had at least one type of new antiepileptic drugs. The first and second most ones were lamotrigine and oxcarbazepine. Drug resistant epilepsy was concerned as problematic condition in most physicians (82.4%) but only 54.5% of them had experiences referring patient for epilepsy surgery. Conclusions: Epilepsy treatment gap has still been important health care problem, especially in difficult to treat epileptic patients commonly seen in secondary hospitals. Further medical care resources in epilepsy need to be ascertained for more accurate information.